2016
DOI: 10.6007/ijarbss/v6-i11/2375
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Perception of Taxpayers towards Goods and Services Tax (GST) Implementation

Abstract: Announcement the proposed implementation of Goods and Services Tax (GST) are made by the Prime Minister of Malaysia in Budget 2005. However, the implementation has been delayed and the government has made decision to implement it on April 2015, as they are wanted to receive public feedback before implementing it. Until now, many communities are less understanding and confused regarding GST system and give a negative perception about it. Accordingly, this study attempts to find out what level of awareness and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…They also added that it is because their supplies that will be needed in their operation could be taxable to GST, which would lead to increase in cost of continuing their business. Ahmad et al (2016) found that it is important to give awareness among the SMEs in order for those companies to survive with GST and comply with any GST requirements.…”
Section: H2: There Is a Difference Between Business Size And Problemsmentioning
confidence: 99%
“…They also added that it is because their supplies that will be needed in their operation could be taxable to GST, which would lead to increase in cost of continuing their business. Ahmad et al (2016) found that it is important to give awareness among the SMEs in order for those companies to survive with GST and comply with any GST requirements.…”
Section: H2: There Is a Difference Between Business Size And Problemsmentioning
confidence: 99%
“…Mohamad Ali Roshidi Ahmad, Zuriadah Ismail, and Hazianti Abdul Halim (2016) [12] introducing the GST in Malaysia, government should have careful planning, detailed preparation, participation of community and extensive public education program is the key success in the implementation of GST for any country (Mohamad Ali Roshidi Ahmad¹*, 2016) [12] Shefali Dani (2016) [16] GST will simplify existing indirect tax system and will help to remove inefficiencies created by the prevailing current heterogeneous taxation system as long as there's transparent consensus over issues of threshold limit, revenue rate, and inclusion of petroleum products, electricity, liquor and real estate. Anil Kumar Bhuyan, Ranusaya Nayak (2017) [2] the implementation of the GST will be too delayed because of the conflict between state and center on issues related to the limitation of fiscal autonomy of states, constitutional amendments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…GST will reduce the average tax burden of the customer and it will bring transparency to the system. Ahmad et al (2016) discussed the implementation of GST, which was introduced in April 2015 in Malaysia. The objectives of the study were to review the perception and acceptance of the taxpayer towards the implementation of GST.…”
Section: Indian Handicraft Sectormentioning
confidence: 99%